The Charismatic Leadership of Prof. Imam Suprayogo in Improving The Quality of Education - Kartika Hudayana; Imron Arifin; Juharyanto Juharyanto; Imam Mujahid (STKIP Singkawang, 2023)
Prof. Imam Suprayogo is a Maulana Malik Ibrahim State Islamic University professor and was the campus's rector. Charismatic leadership is a leadership style owned by Prof. Imam Suprayogo. Many figures admire the figure of Prof. Imam Suprayogo, a leader who develops institutions while developing people in his institutions and a promoter of the advancement of Islamic Higher Education, especially in improving the quality of his education. This research uses a qualitative approach with a descriptive type of research. The researcher collected the data using interviews, observations, and documentation. The analysis techniques use interactive analysis techniques. The implementation of the validity of the data is carried out by checking credibility, dependability, and confirmability. The results of the study revealed that there are five characteristics of charismatic leadership used by Prof. Imam Suprayogo in improving the quality of education, namely: (1) exemplary, (2) linguistics/rhetoric, (3) silaturahim/sowan, (4) compassion, (5) participation, and (6) function approach.